STRATEGI KOMUNIKASI TIM GUGUS TUGAS COVID-19 DALAM PELAKSANAAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) - Silmi Salimah; Reni Nuraeni, Ph.D.; Rizca Haqqu, M.Ikom. (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
The purpose of this study was to determine the implementation of the communication strategy carried out by the Head of the Tasikmalaya City Covid-19 Cluster Team in the implementation of Large-Scale Social Restrictions (PSBB). The research method used is a qualitative method with data collection techniques interview, observation and documentation. The results showed that the implementation of the communication strategy carried out by the Task Force Team of the City of Tasikmalaya was in accordance with the indicators of the communication strategy ranging from the communicator determination strategy, message determination strategy, media determination strategy and audience determination strategy. The communication strategy implemented resulted in the fact that the spread of Covid-19 in Tasikmalaya City had decreased due to the implementation of discipline carried out by the apparatus as the Tasikmalaya City Covid-19 Task Force Team and communication that was conveyed to the public with the right strategy. The implementation of the communication strategy that has been carried out by the Task Force Team, the implementation of the report on the results of the Tasikmalaya City discipline presentation is reported directly to the Governor who is charged to Kominfo with the local Government.